Spinal anesthesia causing hearing loss: are we aware? (Bangladesh Journal of Medical Science, 2014)
Sensorineural hearing loss can be attributed to many factors. Acoustic trauma, noisy environment, genetic syndromes, inner ear infection and tumors are the known well-established causes. Some of them are treatable but many of those are nonreversible. Recent literatures have shown some data that suggest this type of hearing loss also occurring post anesthesia, particularly in spinal anesthesia cases. Others claim that this hearing loss is temporary and clinically not significant. DOI: http://dx.doi.org/10.3329/bjms.v13i3.19136 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.251-254